PENGARUH PENDEKATAN PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA - M Sunu Probo Baskoro (LPPM STAI Haji Agus Salim, 2025)
This research aims to examine the impact of learning approaches on students' academic achievement. Various learning approaches, including teacher-centered and student-centered approaches, are analyzed to see how each influences students' academic performance across different subjects. The method used in this research is a quasi-experiment, where two groups of students were given different learning approaches, and their learning outcomes were compared. Data were collected through achievement tests conducted before and after the intervention, as well as through observations and questionnaires related to student engagement during the learning process. The results of the study show that the student-centered learning approach significantly enhances student engagement and learning outcomes compared to the teacher-centered approach. Students who learned through the student-centered approach demonstrated improvements in critical thinking, creativity, and problem-solving skills. Meanwhile, the teacher-centered approach was more effective in delivering information quickly but was less supportive of developing collaborative skills and active student participation. The study concludes that the use of student-centered learning approaches can have a greater long-term positive impact on learning outcomes, particularly in the context of 21st-century education, which emphasizes higher-order thinking skills.